The effect of litigation risks to earnings management using audit quality as moderating variable - Titis Puspitaningrum Dewi Kartika; Joicenda Nahumury (Universitas Hayam Wuruk Perbanas, 2014)
In agency theory, a company, which separates the functions of governance and ownership, is going to be susceptible to the agency conflicts. The arising agency conflict causes the information, which is provided by manager becoming different or can be manipulated. One of common practice done by manager is earning management, where earning management is an accounting policy choice conducted by the managersfor the variety of specific purposes. This study tries to reveal whether audit qualities are able to reinforce the association between litigation risks to the earning management practice. Auditor litigation has 14 characteristics of companies being able to be auditor litigation by calculating LITSCORE. Earnings management is proxied by The Modified Jones Model while audit quality is proxied by industry specialization. This study uses financial statements data of the manufacturing companies listed in Indonesia Stock Exchange in 2010-2012. Analysis, which is used in this study, is the MRA(Moderated Regression Analysis). The results of this study suggest that there is influence between litigation risk to earnings management while audit quality as measured by specialized auditors cannot strengthen relationship between litigation risk and earnings management. This is because audit quality as measured by specialized auditors did not show a strong relationship.